Innovative design and analysis of a longitudinal-torsional transducer with the shared node plane applied for ultrasonic assisted milling. (June 2019) - Wu, Chenjun; Chen, Shijin; Cheng, Kai; Ding, Hui; Xiao, Caiwei
This paper presents an innovative design and development of a longitudinal-torsional ultrasonic vibration transducer. This longitudinal-torsional ultrasonic vibration transducer can be stimulated up by one group of longitudinal piezoelectric ceramics and it has a shared longitudinal and torsional vibration node plane. The longitudinal-torsional ultrasonic vibration transducer consists of two amplitude horns, a mounting flange, and four pieces of axially poled piezoelectric ceramics. Theoretical analysis and formulation of the share vibration node have been studied, which are used to guide the design of the transducer. Five helical grooves are cut off along the circumference of the amplitude horn so as to convert the longitudinal vibration to both longitudinal and torsional vibration at the same time. Simulations have confirmed that each longitudinal-torsional vibration mode has one shared node on the transducer. The vibration amplitude is measured by a laser displacement sensor and the largest longitudinal displacement of longitudinal-torsional ultrasonic vibration transducer reaches 6 µm and torsional displacement reaches 11 mrad when 500Vpp voltage is applied on the transducer. Ultrasonic vibration milling experiments have shown that the longitudinal-torsional ultrasonic vibration transducer has played a great role in the cutting process as the longitudinal-torsional ultrasonic vibration milling decreases the cutting force substantially compared to the convention milling operations.